Analisis Pengaruh Strategi Promosi dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT Exo Point (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
This study aims to analyze the promotion strategy and service quality of PT Exo Point's customer satisfaction. The population used is consumers who have been or are general cleaning service users of PT Exo Point. The research sample was 50 respondents who were taken randomly. The research method used is data collection techniques and through library research and field research studies which include observation and distributing questionnaires directly to customers of PT. ExoPoint. Furthermore, to analyze using a Likert scale. The type of data in this study is quantitative data or in the form of numbers. The results showed that simultaneously promotion strategy and service quality had an effect on customer satisfaction. Partially the promotion strategy has no effect on customer satisfaction. PT Exo Point company should increase promotions and maintain service quality so that customers feel satisfied.